1958
DOI: 10.1017/s008045680000956x
|View full text |Cite
|
Sign up to set email alerts
|

XIX.—Metamorphic History of the Schichallion Complex (Perthshire)

Abstract: SynopsisThe Schichallion complex is situated in the Central Highlands of Scotland between the villages Struan and Kinloch Rannoch. The area is of considerable geological interest and has been investigated stratigraphically and structurally by E. M. Anderson and Bailey and McCallien. As a consequence of their researches a complete stratigraphical succession has been established. Thus, the metamorphic rocks of the area are classified into the Moinian and Dalradian systems, which are separated by a plane of tecto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0

Year Published

1961
1961
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(34 citation statements)
references
References 12 publications
(12 reference statements)
1
33
0
Order By: Relevance
“…This interpretation (Treagus and King, 1978;Treagus, 1987Treagus, , 2000 contradicts previous interpretations (Bailey and McCallien, 1937;Rast, 1958) that this is a folded sequence of formations now assigned to the Blair Atholl Subgroup and the lower Argyll Group, and that the contact with the Grampian Group is a 'slide'.…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations
“…This interpretation (Treagus and King, 1978;Treagus, 1987Treagus, , 2000 contradicts previous interpretations (Bailey and McCallien, 1937;Rast, 1958) that this is a folded sequence of formations now assigned to the Blair Atholl Subgroup and the lower Argyll Group, and that the contact with the Grampian Group is a 'slide'.…”
Section: Discussionmentioning
confidence: 80%
“…This interpretation was supported subsequently by Rast (1958), who interpreted a persistent outcrop of schist immediately above the slide, the Beoil Schist, not as a stratigraphical formation but as a product of localized ductile deformation.…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…Pantin (1961), who introduced the simpler term Glen Banvie ‗Series' for the ‗Blair Atholl Series of the Banvie Burn Belt', found no evidence for sliding at Gilbert's Bridge. However, Harris (1963) interpreted the junction to be a thrust slide carrying the Dalradian rocks to the north-west, and Thomas (1965Thomas ( , 1980 concluded that the Boundary Slide is associated with a tectonic schist equivalent to the Beoil Schist of the Schiehallion area (Rast, 1958) (see the Strath Fionan GCR site report in Treagus et al, 2013).…”
Section: Introductionmentioning
confidence: 99%